Interstices Issue 15: Atmospheres and Affect CFP - Douglas, Andrew; Engels-Schwarzpaul, Tina; Jenner, Ross (Interstices: Journal of Architecture and Related Arts, 1970)
Interstices 15 Moved: On Atmospheres and AffectsDecember 3, 2013Call for PaperWhat does being moved mean, historically and in contemporary senses, for thinking design practices spanning cities, architecture, scenography, interiors, objects? How are atmospheres related to lapsed ideals of subject integrity and to the immersion in affective states? What are the roles, politically, culturally and creatively, of emotion and imagination, and of felt or non-conscious states and excesses of affect, in the context of late capital? Since, more than 50 years ago, cultural theorist Raymond Williams (2001) foregrounded structures of feeling as pivotal to any understanding of cultural complexity, consideration of feeling, intensity, affect and immanent experience has increasingly gained importance across disciplinary areas. More recently, this tendency was echoed in architecture, art and design in an increased attention to atmospheres. Peter Zumthor (2006), for one, has said of atmosphere that it is the means by which “emotional sensibility” is registered as such. As a form of perception operating faster than any critical faculty, it offers orientation to the question “what do we mean when we speak of architectural quality?” This emphasis on the concept of atmosphere – something he shares with designers and theorists as diverse as Olafur Eliasson, James Turrell, Jean-Gilles Decosterd & Philippe Rahm, Herzog & de Meuron, Diller & Scofidio, Juhani Pallasmaa and Tim Ingold – finds common reference in the thinking of German philosopher Gernot Böhme.For Böhme, in Architektur und Atmosphäre (2006) particularly, atmospheres affect our primary aesthetic reality. What he calls atmosphere – mood and affect in their spatial situation – is the primary reality aesthetics has to deal with. These are what the beholder of a work of art and what that beholder perceives have in common. We talk of the feel or mood of a space, but not of a thing or object. Atmosphere demands a co-presence that necessary engulfs the terms of any subject/object division; it is this primary reality, where moods and affects play a key role, that aesthetics – itself understood as aesthesis or a general theory of perception – must deal with. Such a theory must lead to a confrontation with the longstanding bifurcation of what the Greeks defined as physis and techné, or nature and technology, and indeed calls for something like a revision in understanding of what mediation as perception entails.It is no surprise that the first accounts of architectural space in modernity arose from conceptions of bodily experience, for example, in Schmarsow’s account of architectural space (1894). Already in 1851, Mrs Merrifield used the notion of atmosphere to describe the Crystal Palace, which “is perhaps the only building in the world in which atmosphere is perceptible” (1970). Gottfried Semper, who also participated in the Great Exhibition, was perhaps the first architect to theorise atmosphere, arguing in 1860: “every artistic creation, every artistic pleasure, presumes a certain carnival spirit, or to express it in a modern way, the haze of carnival candles is the true atmosphere of art.” (2004). Jean Baudrillard recognized in modernity an increasing lapse of harmony, or Stimmung, between self, objects and their associated worlds. Pockets of interiority, which once stabilized these associations, increasingly open to linkages that have no predefined syntax, propriety or taste. In his “sociology of interior design”, what counts is not bourgeois space as tasteful signature of an owner or crafter, but a new de-subjectified domain. The subject becomes “an active engineer of atmospheres” (2002). In such environments, the rhetoric of personification reigns: “the atmosphere will be yours alone” (2002). Yet, this modeling of agency arises precisely in a context where ‘the interior’ loses its sheltering capacity and is subjected to invasive, affective processes. Everything – from the economy, to political stability, to the future prospects of the planet – is moodily bathed in gloom, indifference or saccharine buoyance.For Böhme, such affective immersion corresponds with a double movement in modernity’s “technological civilization”. On one hand, such a civilization is predicated on a “decidedly unemotional stance” while, on the other, it fosters the “development of an enormous imaginary domain” nurturing an otherwise truncated emotionality (2012). Affectively calibrated environments are inseparable from an “invasive technification” and externalization of social constraint. The production of commodity atmospherics has become part of architectural, design and art practice.We invite you to contribute to the forthcoming issue “Moved: On Atmospheres and Affects” – in its refereed or non-refereed part. Interstices accepts both academic and practice oriented, fully written as well as visual, contributions that engage with the issue theme. For the double blind refereed part, we welcome submission of 5000 word papers and visual submissions with an accompanying text of approximately 500 words. For the non-refereed part, we welcome papers up to 2500 words and project reports and reviews of up to 1000 words. Visit our website to check out the Guidelines for Submissions for details about the reviewing process, copyright issues and formatting: http://interstices.ac.nz/information-for-contributors/guidelines-for-submissions/Please send your submission to Andrew Douglas (adouglas@aut.ac.nz) by 15 February 2014. Authors accepted for the reviewing process will receive confirmation and a schedule in late February, and the journal will be published in November 2014.We look forward to your contribution!Issue Editors: Andrew Douglas, Tina Engels-Schwarzpaul  and Ross Jenner References:Baudrillard, J. (2002). Structures of interior design. In B. Highmore (Ed.), The everyday reader (pp. 308-318). London, England: Routledge.Böhme, G. (2006). Architektur und Atmosphäre. München, Germany: Wilhelm Fink Verlag.Böhme, G. (2012). Invasive technification: Critical essays in the philosophy of technology (C. Shingleton, Trans.). London, England: Bloomsbury Academic.Merrifield, M. P. (1970). Essay on the Harmony and Contrast of Colours as Exemplified in the Exhibition. In The Arts Journal Illustrated Catalogue: The Industry of All Nations, 1851. London, England: David & Charles.Schmarsow, A. (1894). Das Wesen der architektonischen Schöpfung: Antrittsvorlesung gehalten in Leipzig 1893. Leibzig, Germany: Hiersemann.Semper, G. (2004). Style in the technical and tectonic arts; or, practical aesthetics (H. F. Mallgrave & M. Robinson, Trans.). Los Angeles, CA: Getty Research.Williams, R. (2001). The Long Revolution. Peterborough, ON: Broadview Press.Zumthor, P. (2006). Atmospheres: Architectural environments; surrounding objects. Basel, Switzerland: Birkhäuser.